2023
DOI: 10.1037/pag0000751
|View full text |Cite
|
Sign up to set email alerts
|

Optimal cognitive offloading: Increased reminder usage but reduced proreminder bias in older adults.

Abstract: Research into prospective memory suggests that older adults may face particular difficulties remembering delayed intentions. One way to mitigate these difficulties is by using external reminders but relatively little is known about age-related differences in such cognitive offloading strategies. We examined younger and older adults’ (N = 88) performance on a memory task where they chose between remembering delayed intentions with internal memory (earning maximum reward per item) or external reminders (earning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…Interestingly, metacognitive judgments revealed that older (but not younger) adults were overconfident in their ability to complete the task without reminders, which may explain why they did not use reminders more frequently when given the option. Using a similar procedure, Tsai et al (2023) also found that older adults used reminders less frequently than is optimal based on their own internal memory abilities.…”
Section: Prospective Memory Offloadingmentioning
confidence: 88%
See 3 more Smart Citations
“…Interestingly, metacognitive judgments revealed that older (but not younger) adults were overconfident in their ability to complete the task without reminders, which may explain why they did not use reminders more frequently when given the option. Using a similar procedure, Tsai et al (2023) also found that older adults used reminders less frequently than is optimal based on their own internal memory abilities.…”
Section: Prospective Memory Offloadingmentioning
confidence: 88%
“…showed that older adults were overconfident in their ability to complete the task under high load without reminders. From a metacognitive viewpoint of PM offloading, overconfidence by older adults should have resulted in less frequent reminder checking when given the opportunity (Tsai et al, 2023). Notably, Scarampi and Gilbert (2020) found that older adults were also overconfident in their unaided memory ability under high load using the intention offloading task, yet older adults did not use reminders more often to compensate for poorer unaided memory ability when given the option.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cognitive offloading strategies are influenced by metacognitive judgements (i.e. people tend to set reminders when they think that they will otherwise forget, not necessarily when they will actually forget; Boldt & Gilbert, 2019, 2022; Gilbert, 2015b; Gilbert et al, 2020) and are associated with age-related change (Bulley et al, 2020; Redshaw et al, 2018; Scarampi & Gilbert, 2021; Tsai et al, 2023). For a review of these findings, see Gilbert et al (2023).…”
mentioning
confidence: 99%